2004
DOI: 10.31729/jnma.590
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising in Mature Cystic Teratoma

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…On review, quite limited cases of mature cystic teratoma of ovary with squamous cell carcinoma arising from it have published by Nepalese authors till now . Bashyal et al reported three cases of squamous cell carcinoma arising MCT; among them, one of the patients was a young patient aged 33 years.…”
Section: Discussionmentioning
confidence: 99%
“…On review, quite limited cases of mature cystic teratoma of ovary with squamous cell carcinoma arising from it have published by Nepalese authors till now . Bashyal et al reported three cases of squamous cell carcinoma arising MCT; among them, one of the patients was a young patient aged 33 years.…”
Section: Discussionmentioning
confidence: 99%